Respuesta :

Answer:

The solution to the system of equations will be:

[tex]x=0,\:y=-\frac{11}{5}[/tex]

Step-by-step explanation:

Given the expression

[tex]x - 5y = 11[/tex]

[tex]3x - 5y = 11[/tex]

solving the expression

[tex]\begin{bmatrix}x-5y=11\\ 3x-5y=11\end{bmatrix}[/tex]

Multiplying x-5y = 11 by 3:  3x-15y=33

so

[tex]\begin{bmatrix}3x-15y=33\\ 3x-5y=11\end{bmatrix}[/tex]

and

[tex]3x-5y=11[/tex]

[tex]-[/tex]

[tex]\underline{3x-15y=33}[/tex]

[tex]10y=-22[/tex]

now solving 10y = -22 for y

[tex]10y=-22[/tex]

divide both sides by 10

[tex]\frac{10y}{10}=\frac{-22}{10}[/tex]

simplify

[tex]y=-\frac{11}{5}[/tex]

For 3x-5y=11 plug in y = -11/5

[tex]3x-15\left(-\frac{11}{5}\right)=33[/tex]

[tex]3x+15\cdot \frac{11}{5}=33[/tex]

[tex]3x+33=33[/tex]

Subtract 33 from both sides

[tex]3x+33-33=33-33[/tex]

Simplify

[tex]3x=0[/tex]

Divide both sides by 3

[tex]\frac{3x}{3}=\frac{0}{3}[/tex]

Simplify

[tex]x=0[/tex]

Thus, the solution to the system of equations will be:

[tex]x=0,\:y=-\frac{11}{5}[/tex]

ACCESS MORE